Hadith #1100 - Sahih Muslim - Tawus bin Kaysan طاوس (Sahih Muslim)
We asked Ibn Abbas about sitting on one’s buttocks (in prayer). (ala alqad mein) He said: It is sunnah. We said to him: We find it a sort of cruelty to the foot. Ibn ‘Abbas said: It is the sunnah of your Apostle (ﷺ).
Grade: Sahih

Hadith #1853 - Sahih Muslim - Tawus bin Kaysan طاوس (Sahih Muslim)
I asked Ibn Abbas it one should apply to oneself perfume or oil which is available with his wife. He (Ibn Abbas) said: I do not know of it.
Grade: Sahih

Hadith #2734 - Sahih Muslim - Tawus bin Kaysan طاوس (Sahih Muslim)
Narrate how you informed me about the meat of the game presented to the Messenger of Allah (ﷺ) as he was in the state of Ihram. Thereupon he said: He was presented with a slice of the meat of game, but he returned it to him (who presented it) saying: We are not going to eat it, as we are in the state of Ihram.
Grade: Sahih

Hadith #3099 - Sahih Muslim - Tawus bin Kaysan طاوس (Sahih Muslim)
I was in the company of Ibn Abbas (Allah be pleased with them) when Zaid b. Thabit said: Do you give religious verdict that the woman who is in menses is allowed to go without performing the last circumambulation of the House? Ibn ‘Abbas (Allah be pleased with them) said to him: Ask such and such woman of the Ansar, if you do not (believe my religious verdict) whether Allah’s Messenger (ﷺ) had coimmanded her this. Zaid b Thabit (went to that lady and after getting this verdict attested by
Grade: Sahih

Hadith #3829 - Sahih Muslim - Tawus bin Kaysan طاوس (Sahih Muslim)
I said to him: Abu Abd al-Rahrman, I wish if you abandon this renting of land, for they alleged that Allah’s Apostle (ﷺ) forbade Mukhabara. He siad: Amr, one who has informed me has the best knowledge of it among them (he meant Ibn Abbas). (He said) that Allah’s Apostle (ﷺ) did not prohibit it altogether, but said: Lending of land by one among you to his brother is better for him than getting a specified amount of produce from it.
Grade: Sahih

Hadith #4014 - Sahih Muslim - Tawus bin Kaysan طاوس (Sahih Muslim)
Distribute the property amongst Ahl al-Fara’id, according to the Book of Allah, and what is left out of them goes to the nearest male heir.
Grade: Sahih

Hadith #6587 - Sahih Muslim - Tawus bin Kaysan طاوس (Sahih Muslim)
I found some Companions of Allah’s Messenger (ﷺ) as saying: Everything is by measure. And he further said: I heard Abdullah b. ‘Umar as saying: There is a neasure for everything-even for incapacity and-capability.
Grade: Sahih